White Matter Integrity in Highly Traumatized Adults With and Without Post-Traumatic Stress Disorder - Fani, Negar (Nature Publishing Group, 2012)
Prior structural imaging studies of post-traumatic stress disorder (PTSD) have observed smaller volumes of the hippocampus and cingulate cortex, yet little is known about the integrity of white matter connections between these structures in PTSD samples. The few published studies using diffusion tensor imaging (DTI) to measure white matter integrity in PTSD have described individuals with focal trauma rather than chronically stressed individuals, which limits generalization of findings to this population; in addition, these studies have lacked traumatized comparison groups without PTSD. The present DTI study examined microstructural integrity of white matter tracts in a sample of highly traumatized African-American women with (n=25) and without (n=26) PTSD using a tract-based spatial statistical approach, with threshold-free cluster enhancement. Our findings indicated that, relative to comparably traumatized controls, decreased integrity (measured by fractional anisotropy) of the posterior cingulum was observed in participants with PTSD (p<0.05). These findings indicate that reduced microarchitectural integrity of the cingulum, a white matter fiber that connects the entorhinal and cingulate cortices, appears to be associated with PTSD symptomatology. The role of this pathway in problems that characterize PTSD, such as inadequate extinction of learned fear, as well as attention and explicit memory functions, are discussed.